PARADIGMATIC RELATIONS IN THE UZBEK LANGUAGE (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The importance and study of the concept of paradigm in linguistics, the views of linguists regarding the concept of paradigm are highlighted in the article. It is based on the researches of scientists in bringing scientific opinions that the paradigm of gradation, the manifestation of graduonymy as a linguistic paradigm, and the fact that graduonymy is a paradigm is considered a type of paradigmatic relation.